Unbuttoned: The Interaction Between Provocativeness of Female Work Attire and Occupational Status - Orakçıoğlu, İsmail (Springer/Plenum Publishers, 2015)
Gender-biased standards in United Kingdom (UK) workplaces continue to exist. Women experience gender discrimination in judgements of competence, even by other women. Clothing cues can subtly influence professional perceptions of women. The aim of this study was to investigate how minor manipulations to female office clothing affect the judgements of competence of them by other UK females and to examine whether such effects differ with occupational status. One group of female university students (n = 54) and one group of employed females (n = 90), all from London and the East of England, rated images of faceless female targets, on a global competence measure derived from six competence ratings (of intelligence, confidence, trustworthiness, responsibility, authority, and organisation). The dress style was conservative but varied slightly by skirt length and the number of buttons unfastened on a blouse. The female targets were ascribed different occupational roles, varying by status (high - senior manager, or low - receptionist). Participants viewed the images for a maximum of 5 s before rating them. Overall participants rated the senior manager less favourably when her clothing was more provocative, but more favourably when dressed more conservatively (longer skirt, buttoned up blouse). This interaction between clothing and status was not present for the receptionist. Employed participants also rated females lower than did student participants. We conclude that even subtle changes to clothing style can contribute towards negative impressions of the competence of women who hold higher status positions in a UK cultural context.
Keywords: Female workplace attire; Occupational status; Gender bias; Female perceptions; UK gender beliefs; Competence